Glycomyces buryatensis sp. nov., an actinobacterium isolated from steppe soil. Issue 2 (6th December 2019) - Nikitina, Elena; Liu, Shao-Wei; Li, Fei-Na; Buyantueva, Lyubov; Abidueva, Elena; Sun, Cheng-Hang
Abstract : A novel actinobacterial strain, designated 18 T, was isolated from a steppe soil sample collected in Buryatia, Russia and subjected to polyphasic taxonomic characterization. The strain was aerobic and Gram-stain-positive. The 16S rRNA gene sequence of strain 18 T exhibited highest similarity to Glycomyces paridis CPCC 204357 T (97.2 %). Results of phylogenetic analysis showed that strain 18 T formed a distinct branch clearly affiliated to the genus Glycomyces . Whole-cell hydrolysates of the isolate contained meso -diaminopimelic acid as the cell-wall diamino acid. The whole-cell sugar profile was found to contain galactose, glucose, ribose and xylose. MK-10(H4 ) and MK-11(H4 ) were the predominant menaquinones. The polar lipid profile consisted of diphosphatidylglycerol, phosphatidylglycerol, five unidentified phospholipids and four unidentified polar lipids. The major fatty acids identified were anteiso-C15 : 0 and iso-C15 : 0 . The G+C content of the genomic DNA of strain 18 T was 68.0 mol% (draft genome sequence). Based on its phylogenetic, phenotypic and chemotaxonomic features, strain 18 T was considered to represent a novel species of the genus Glycomyces, for which the name Glycomyces buryatensis sp. nov. is proposed. The type strain of Glycomyces buryatensis is 18 T (=JCM 33362 T =CGMCC 4.7610 T ).